Experimental and numerical investigation of the operating performance of air-to-air membrane enthalpy exchangers. (February 2022) - Albdoor, Ahmed K.; Ma, Zhenjun; Al-Ghazzawi, Fatimah; Liu, Jingjing; Awan, Muhammed B.
Highlights: The performance of a membrane enthalpy exchanger was assessed experimentally. Effects of the operating parameters on the performance were investigated. A mathematical model was developed to obtain transmembrane heat and mass fluxes. Ambient conditions slightly affect the membrane enthalpy exchanger performance. Abstract: This study examined the impacts of major operating parameters on the performance of a cross flow membrane enthalpy exchanger (MEE) with porous membranes. A lab-scale setup was developed to conduct the experiments based on the test matrix designed with various operating conditions for both heating and cooling operations. The MEE core was made of porous membranes. A mathematical model was developed to predict the transferred heat and moisture fluxes through the membrane. The model implemented a variable moisture diffusivity of the membrane that varied with local air conditions. It was found that the sensible, latent, and total effectiveness of the MEE significantly improved when reducing the airflow rate. In the cooling mode, outdoor air temperature and humidity had a positive influence on the MEE effectiveness, while they showed a negative impact on the heating operations. However, the influences of outdoor conditions on the sensible, latent, and total effectiveness of the MEE were rather insignificant as compared to that of the airflow rate. On the other hand, both airflow rate and outdoor conditions showed significant effects on thermal resistance and total energy recovered for both operating modes. The findings obtained can be used to facilitate optimal design of such devices.